MENINGKATKAN KETERAMPILAN GURU DI MASA PANDEMI COVID 19 DENGAN MENGEFEKTIFKAN SUPERVISI TEKNIK KUNJUNGAN KELAS DI SDN TEMBALANG SEMARANG - Astuti, Endang Rahayu (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
Teachers are required to be able to take advantage of various online learning applications while still emphasizing the creation of communicative learning and being able to activate students' thinking power, but not all teachers, including teachers at SDN Tembalang, Semarang City, are able to utilize these various applications to improve their teaching skills, teachers still use this pattern. face-to-face learning or only able to provide learning assignments without showing their teaching skills, so that students are burdened with the learning carried out. Of the 16 teachers at SDN Tembalang, Semarang City, only 8 teachers or 50% are skilled at teaching during the pandemic with various applications being used. This study is intended to answer the question of whether supervision with class visit techniques can improve the skills of teaching teachers during the COVID-19 pandemic at SDN Tembalang, Semarang City, for the 2020/2021 Academic Year? These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that there was an increase in the skills of teaching teachers during the COVID-19 pandemic through supervision with class visit techniques at SDN Tembalang, Semarang City in the 2020/2021 academic year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in cycle I there are 11 teachers or 69% and in the second cycle there are 15 teachers or 94%. These results indicate that these results are in line with expectations. The increase in the implementation of the class visit technique is an effective way for school principals to improve teacher skills in teaching.